Shortened Penetratin Cell-Penetrating Peptide Is Insufficient for Cytosolic Delivery of a Grb7 Targeting Peptide - Watson, Gabrielle M; Kulkarni, Ketav; Brandt, Rebecca; Del Borgo, Mark P; Aguilar, Marie-Isabel; Wilce, Jacqueline A (ACS omega, 2017)
Delivery across the cell membrane is of critical importance for the development of therapeutics targeting intracellular proteins. The use of cell-penetrating peptides (CPPs), such as Penetratin (P16), has facilitated the delivery of otherwise cell-impermeable molecules allowing them to carry out their biological function. A truncated form of Penetratin (RRMKWKK) has been previously described as the minimal Penetratin sequence that is required for translocation across the cell membrane. Here, we performed a detailed comparison of cellular uptake by Penetratin (P16) and the truncated Penetratin peptide (P7), including their ability to deliver G7-18NATE, a cyclic peptide targeting the cytosolic cancer target Grb7-adapter protein into cells. We identified that both P16 and P7 were internalized by cells to comparable levels; however, only P16 was effective in delivering G7-18NATE to produce a biological response. Live-cell imaging of fluorescein isothiocyanate-labeled peptides suggested that while P7 may be taken up into cells, it does not gain access to the cytosolic compartment. Thus, this study has identified that the P7 peptide is a poor CPP for the delivery of G7-18NATE and may also be insufficient for the intracellular delivery of other bioactive molecules.